wingless signal and zeste-white 3 kinase trigger opposing changes in the intracellular distribution of armadillo. - Peifer, M.; Sweeton, D.; Casey, M.; Wieschaus, E. (Development, 1994)
wingless/wnt-1 signaling directs cell fate during development. Genetic analysis in Drosophila identified genes that may encode components of the wingless signal transduction system. Drosophila Armadillo, homolog of vertebrate beta-catenin, is required for wingless signaling. Unlike armadillo RNA, Armadillo protein accumulates non-uniformly in different cells of each embryonic segment. We found that cells alter their intracellular distribution of Armadillo in response to Wingless signal, accumulating increased levels of cytoplasmic Armadillo relative to those of membrane-associated protein. Levels of cytoplasmic Armadillo are also regulated by Zeste-White 3 kinase. Analysis of double mutants demonstrates that Armadillo's role in wingless signaling is direct, and that Armadillo functions downstream of both wingless and zeste-white 3. We present a model for the role of Armadillo stripes in transduction of wingless signal.